The combustion, performance and emissions investigation of a dual-fuel diesel engine using silicon dioxide nanoparticle additives to methanol. (1st September 2021) - Wei, Jiangjun; He, Chengjun; Lv, Gang; Zhuang, Yuan; Qian, Yejian; Pan, Suozhu
Abstract: The study made investigation on the combustion, performance and emissions of a modern dual fuel (DF) diesel engine using silicon dioxide (SiO2 ) nanoparticle additives to methanol under different test conditions. The tests were conducted in three operating modes: diesel mode; methanol/diesel mode (methanol mode for short) and methanol-based SiO2 nanofluid (MSN)/diesel mode (MSN mode for short) where the MSN was injected in the intake manifold. The results displayed that nano-SiO2 inclusion in methanol increased the peak pressure by 8.6% in maximum and peak heat release rate by 4.3% in maximum. The brake thermal efficiency (BTE) and brake specific fuel consumption (BSFC) were improved with all the tested dosages of SiO2 nanoparticles in the fuel, especially under high load conditions, the improvements of 5.1% in maximum and 6.2% in maximum for BTE and BSFC were achieved. Compared with the cases in methanol mode, CO, HC, NOx and smoke opacity in MSN mode were reduced by 38.5%, 55.4%, 5.2% and 55.6%, respectively. All the results indicate that the addition of SiO2 nanoparticle in methanol could enhance the combustion and performance characteristics, and suppress the emissions of the DF diesel engines. Highlights: Nano-SiO2 addition increases HRRmax and Pmax, especially at high engine load. SiO2 nanoparticles cause obvious ignition and combustion duration improvements. Nano-SiO2 additives in methanol increase BTE and lessen BSFC. SiO2 nanoparticles suppress significantly CO, HC, NOX and smoke emissions.